2011
DOI: 10.1371/journal.pone.0020617
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Mitochondria in Immune-Mediated Apoptotic Death of the Human Pancreatic β Cell Line βLox5

Abstract: Mitochondria are indispensable in the life and death of many types of eukaryotic cells. In pancreatic beta cells, mitochondria play an essential role in the secretion of insulin, a hormone that regulates blood glucose levels. Unregulated blood glucose is a hallmark symptom of diabetes. The onset of Type 1 diabetes is preceded by autoimmune-mediated destruction of beta cells. However, the exact role of mitochondria has not been assessed in beta cell death. In this study, we examine the role of mitochondria in b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 74 publications
0
19
0
Order By: Relevance
“…63,64,77 In the absence of Fas-associated protein with death domain-like IL-1b-converting enzyme inhibitory protein, Fas receptors induce apoptosis via both caspase-dependent and independent pathways. 69,[77][78][79] Protracted stimulation of IL-1b promotes apoptosis by downregulating other protective proteins within the b cell. 64,80 In addition, both Fas activation and IL-1b induce mitochondrial dysfunction 77 and in vitro studies of b cells in NODAT have demonstrated a role for mitochondrial dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…63,64,77 In the absence of Fas-associated protein with death domain-like IL-1b-converting enzyme inhibitory protein, Fas receptors induce apoptosis via both caspase-dependent and independent pathways. 69,[77][78][79] Protracted stimulation of IL-1b promotes apoptosis by downregulating other protective proteins within the b cell. 64,80 In addition, both Fas activation and IL-1b induce mitochondrial dysfunction 77 and in vitro studies of b cells in NODAT have demonstrated a role for mitochondrial dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…However, these cell lines have proven to be valuable tools for other in vitro applications, especially immunological studies [6]. Specifically, the adult beta cell-derived βLox5 cell line has been essential in uncovering the role of mitochondria in Fas and proinflammatory cytokine-mediated beta cell death [7]. Additionally, βLox5 cells express relevant T1D autoantigens and, similar to primary islets, display upregulation of major histocompatibility complex (MHC) class I on priming with interferons, making them excellent beta cell surrogates in cell-mediated lymphocytotoxicity assays.…”
Section: Lessons Learned From Current Beta Cell Linesmentioning
confidence: 99%
“…In a population-based study of 385 Japanese patients (154 male and 231 female) with T1D and 469 age-and sex-matched controls, the methionine-containing allele was associated with protection from T1D (p = 0.017) and a significantly reduced frequency (p = 0.0046) of the T1D-associated auto-antibodies (GAD, IA-2, and IAA). To study the impact of mt-ND2 a on human beta-cell destruction, cytoplasmic hybrid (or cybrid) human beta-cells were generated by fusing mitochondrial DNA-depleted human beta-cells with platelets [57,58], because they are anuclear. Platelet donors were chosen based on their mtDNA haplotype [59][60][61].…”
Section: Mt-nd2 and Mt-nd2mentioning
confidence: 99%
“…To study the impact of mt-ND2 a on human beta-cell destruction, cytoplasmic hybrid (or cybrid) human beta-cells were generated by fusing mitochondrial DNA-depleted human beta-cells with platelets [57,58], because they are anuclear. Platelet donors were chosen based on their mtDNA haplotype [59][60][61]. Individuals from haplogroup D served as donors for the mt-ND2 a -containing human beta-cell lines, while platelets from donors with haplogroup M9 were fused to produce the mt-ND2 c -containing human beta-cells.…”
Section: Mt-nd2 and Mt-nd2mentioning
confidence: 99%